Correlation of foot dimensions with body weight - A study in young population of central India - Sundip H. Charmode; H.S. Kadlimatti (Elsevier, 2019)
Background and objective: Identifying a human individual through scientific means is a key component of forensic investigation. Anatomists, forensic scientists, anthropologists, physicians, podiatrists, and numerous other groups all over the world have studied human foot in different ways. In developing countries like India, people tend to walk barefooted for various reasons like spiritual thoughts, religious reasons, during socio-cultural events, climatic condition, in rural areas and due to socio-economic reasons. This increases the importance of foot impression for forensic investigation. Previous studies conducted in Central India have yielded insignificant results. Hence this study was conducted over a large sample size with many variables aiming to develop a database useful for forensic investigation. Methodology: This cross-sectional study was conducted amongst 1000 participants (500 male and 500 female) of ESIC Institute Gulbarga over a period of 14 months. Foot length, foot breadth along with body weight was measured. Results: Mean weight (male) was 58.21 kg and female was 50.14 kg. Statistically significant correlation was observed between body weight and foot dimensions of both sides in both sexes. Correlation coefficient 'r' and Linear regression equation was calculated. Interpretation and conclusion: Statistically significant correlation was observed between body weight and foot dimensions of both sides in both sexes. This data would be useful for forensic investigations and anthropometric studies. Keywords: Correlation, Foot length, Foot breadth, Body weight, Linear regression coefficient, Crime, Barefoot